Sentidos da violência em Sérgio Sant'Anna - Mesquita, Rodrigo de Lima Bento (2010)
The intention of this dissertation is to analyze de meanings that violence can manifest in Sérgio Sant Anna s work. For this, had been chosen eight narratives that present it under diverse prisms. They are: Assassino, O embrulho da carne, Pela janela, Composição I, O Pelotão, Notas de Manfredo Rangel, repórter (a respeito de Kramer), O monstro e Um crime delicado. The examination begins by configuration of this trend in contemporary literature, divides into four sections and, without losing of eye Clément Rosset s Cruelty principle, ends in a dialogue with Martin Heidegger s Basis principle, when we propose the thesis of bottomless well.